ChemInform Abstract: Understanding Ferroelectricity in Layered Perovskites: New Ideas and Insights from Theory and Experiments. Issue 32 (August 2015) - Benedek, Nicole A.; Rondinelli, James M.; Djani, Hania; Ghosez, Philippe; Lightfoot, Philip
Abstract Review: 160 refs.